EFFECT OF VITAMIN E SUPPLEMENTATION ON SPERM MORPHOLOGY AND SEMEN CHARACTERISTICS OF RABBIT BUCKS (FUDMA JOURNAL OF SCIENCES, 2022)
Twenty mixed breed rabbit bucks aged between 6–8 weeks with an average weight of 861g were randomly assigned to four (4) dietary treatments with five (5) bucks per treatment in a Completely Randomized Design to determine the effect of feeding graded levels of Vitamin E on sperm morphology and semen characteristics of rabbit bucks. The rabbits received graded levels of vitamin E/kg feed (0mg/kg, 20 mg/kg, 40 mg/kg and 60 mg/kg for treatments 1, 2, 3 and 4, respectively). Feed and water were given to the rabbit bucks ad libitum during the experiment. The semen collected was taken to laboratory for sperm morphology and semen characteristics and the data collected were analysed using general linear model procedure of statistical analysis system (SAS). The results revealed that the mean number of normal cells, detached head and mid piece defect were not significantly (P>0.05) different across the treatments. However, the percent abnormal defects percent of free tail and coiled tail were significantly (P
Keywords: Vitamin E, Bucks, Rabbit, Sperm Morphology, Semen